Interactions of proteins with small ionised molecules: electrochemical adsorption and facilitated ion transfer voltammetry of haemoglobin at the liquid|liquid interface - Herzog, G.; Moujahid, W.; Strutwolf, J.; Arrigan, Damien (Royal Society of Chemistry, 2009)
The interaction of proteins with interfaces and surfaces provides a basis for studying their behaviourand methods to detect them. This paper is concerned with elucidation of the mechanism ofelectrochemical detection of haemoglobin (Hb) at the interface between aqueous and organicelectrolyte solutions. The adsorption of Hb at the interface was investigated by alternating current (AC)voltammetry. It was found that addition of Hb to the aqueous phase induced a shift of the potential ofzero charge at the liquid|liquid interface, due to interfacial adsorption of Hb. The influence of thenature and the concentration of the organic phase electrolyte on the electrochemical signal wasinvestigated by cyclic voltammetry (CV). It was found that the electrochemical signal, in the presence ofaqueous phase Hb, was due to the facilitated transfer of the anion of the organic phase electrolyte to theaqueous phase. The transfer current was dependent on both the nature and concentration of theorganic phase electrolyte anion. These results confirm that adsorbed Hb molecules at the liquid|liquidinterface interact with small ionised molecules and facilitate their transfer across the interface. Theresults will provide a basis for both biomolecular detection methods and for the study of protein–smallionised molecule interactions.